Phosphorus and Nitrogen Treatment of Reservoir Water using Zeolite - S.B, Ainun.; R, Kugaann.; M.F, Chow. (International Journal of Engineering and Technology, 2018)
Eutrophication in reservoir and tributaries causes obstruction of water flow and increased concentration of organic matter and plant production. The purpose of this project is to research about development of a cost-effective, affordable, efficient and portable Total Phosphorus (TP) and Total Nitrogen (TN) removal agent, transferrable across the target market to facility owners and individuals in the world. Two types of pellet composition were chosen for this project which is zeolite plus clay and the other one is clay only. Implementing a chemical adsorption technique of a clay-zeolite media is unique to the industry. The project outcome was intended to create and test a bench scale apparatus with engineered adsorption clay-zeolite media, and prepared for further field analysis, such as pH stabilization and many more. From the result analysis, we have found that as the contact time increases, the removal efficiency of the pellets also increases. It is clear that pellet with clay and zeolite composition has a better adsorption rate on removal efficiency about 53% for TP and 82% for TN rather than clay only pellet about 48% TP and 67% TN. Since the synthetic solution has a concentration of 5mg/L for both phosphorus and nitrogen, the only variables are pellet composition, pH, temperature and contact time. Both pellets have their pH increasing as the contact time increases.